ANALYSIS OF THE USE OF THE ILYAS AND DOUGLAS METHOD IN NURSING PLANNING IN HOSPITAL INPATIENTS - Latifah Latifah; Annisa Khoiriah; Nelly Maryam (Bagian Keperawatan Fakultas Kedokteran Universitas Sriwijaya, 2026)
Aim: this study was to determine the needs of nurses scientifically using the Ilyas and Douglas method with a work sampling method in the adult care room at the At-Taqwa Gumawang Islamic Hospital. Method: This research is a type of operational research classified as descriptive research with quantitative data analysis. If the basis for the division is the time of contact of the researcher / observer with the population / sample of the study, this study is a cross sectional study. The population in this study were nurses in the adult care room at the At-Taqwa Gumawang Islamic Hospital, which numbered 25 people, consisting of 18 women and 7 men. Results: The results of research with work sampling techniques on nurse activities are divided into four types of activities, namely direct productive activities (40%), indirect productive activities (32%), unproductive activities (9%) and personal activities (19%). Based on the data, it can be seen how much the percentage of workload each shift, namely the morning shift (88.88%), the afternoon shift (83.92%) and the night shift (57.84%). Conclution: the Ilyas and Douglas formulas have different results, in the Ilyas formula, there are 29 nurses needs, while the Douglas method requires only 18 nurses needs.